Interpreting the Oil Risk Premium: do Oil Price Shocks Matter? - Daniele Valenti; Matteo Manera; Alessandro Sbuelz (Fondazione Eni Enrico Mattei (FEEM), 2018)
This paper provides an analysis of the link between the global market for crude oil and oil futures risk premium at the aggregate level. It offers empirical evidence on whether the compensation for risk required by the speculators depends on the type of the structural shock of interest. Understanding the response of the risk premium to unexpected changes in the price of oil can be useful to address some research questions, among which: what is the relationship between crude oil risk premium and unexpected rise in the price of oil? On average, what should speculators expect to receive as a compensation for the risk they are taking on? This work is based on a Structural Vector Autoregressive (SVAR) model of the crude oil market. Two main results emerge. First, the impulse response analysis provides evidence of a negative relationship between the risk premium and the changes in the price of oil triggered by shocks to economic fundamentals. Second, this analysis shows that the historical decline of the risk premium can be modelled as a part of endogenous effect of the oil market driven shocks.
Keywords: Q40; Q41; Q43; E32; 330; Crude Oil Risk Premium; Bayesian SVAR Model; Oil Price Speculation